Quality of mobile apps for psychological skills training in sport: A MARS-based study - Bonetti R.; Rod B.; Sabourin C.; Hauw D. (Computers in Human Behavior Reports)
Over the last decade, there has been a significant increase in the development of mobile applications to deliver various sports services, including psychological skills training (PST) for athletes. While numerous PST-related apps are available, little attention has been given to their objective quality. This study aimed to assess the current offerings of PST apps in sports, rate their quality, and provide recommendations for future app development. A scoping review of PST-related apps available on the Apple App Store and the Google Play Store (i.e., Android) was conducted, resulting in the retention of 28 apps. The apps used different media types to develop the PST. Of the 28 apps, audios were used by 18 (64%), self-assessment by 13 (46%), videos by 12 (43%), articles by 11 (39%), personalized journals by 7 (25%), and interactions through chatbots by 3 (11%). Overall, the app quality measured through the Mobile App Rating Scale (MARS) failed to meet acceptable standards, with a mean rating of 2.78 (out of 5), and only 10 of the apps received a score that met the acceptable standards. The findings highlight the need for improvement in the development of PST apps to enhance their quality and usability.